POTENSI KORUPSI PADA PEMILIHAN KEPALA DAERAH SERENTAK 2024 - Kelik Endro Suryono; Hartanto (Paulus Law Journal, 2023)
The embodiment of people's democracy, namely the regional head elections from 2017 to 2020, has revealed various problems, which can be considered to have reduced the quality of this political event. Debates continue to occur regarding regional head candidates, even DPR/DPRD member candidates who have committed corruption, and the low level of public trust in political parties. There appears to be a correlation with corruption due to the need for campaign funds related to the choice of regional heads. The scope of corruption in regional head candidates needs to be of concern to all parties, so that the prevalence of corruption in the implementation of regional elections actually increases, and undermines the goals of democracy as a means of realizing people's welfare. On the other hand, political parties as the first door to recruiting regional head candidates have an early detection role, in tracking the track record of the regional head candidates they will nominate. The formulation of the problem that will be studied is how the phenomenon/"shadow of corruption" in the 2024 Simultaneous Pilkada reflects the previous Pilkada, this political behavior is also similar to when there are legislative choices. The method used is normative juridical, then examines secondary data for the 2020 simultaneous regional elections, as a view of the potential that will occur in the 2024 simultaneous regional elections. Regional head candidates who commit corruption or are related to criminal acts of corruption do not have the legitimacy to nominate or be elected regional head.